BEBERAPA FAKTOR YANG MEMPENGARUHI KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS - Putra, Windu Unggun Cahya Jalu; Gunawan, Bambang; Musrah, A. Suyatni; Cipto, Cipto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Diabetes mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels or hyperglycemia, which typically occurs due to an imbalance between insulin production, availability, and demand in the body. The aim of this study was to identify several factors influencing blood glucose levels in diabetes mellitus patients. The study design used in this research was cross-sectional. The study was conducted at the Bangetayu Community Health Center. The study was conducted in February 2024. The population consisted of all DM patients enrolled in the Prolanis program. The sample size was 119 participants. Purposive sampling was used for sample selection. The research instrument employed a questionnaire. Data analysis was performed using univariate and bivariate methods. The results of the study showed a significant association between dietary compliance (p-value: 0.001) and physical activity (p-value: 0.022) with blood glucose levels. It is recommended that health centers enhance the effectiveness of health education programs for diabetes patients regarding the factors that can trigger an increase in blood glucose levels.Keywords: Physical Activity, Diabetes Mellitus, Diet.